ANALISIS KEPEMIMPINAN PEREMPUAN (STUDI KASUS GRACE NATALIE PADA PARTAI SOLIDARITAS INDONESIA) - Rakhmadi, Herlambang Dwi Prasetyo; Subaidi, Subaidi (Universitas Cokroaminoto Yogyakarta, 2023)
Leadership is an important key in running an organization, especially political parties, it takes a capable and qualified leader to lead. History in Indonesia records that only a few political parties carry women as their general chairmen, one of the parties that carry women's general chairman is PSI. PSI appointed Grace Natalie as chairman. The low role of women in politics is the focus of Grace Natalie's leadership at PSI, in addition to focusing on young people and across religions. This research uses library research, namely collecting data by understanding and studying sources from various literature related to the research. Grace Natalie as a leader tries to lead PSI with two types of leadership, namely transformative and feminine leadership types. This type of transformative leadership is seen in the innovation and vision carried out by Grace Natalie, namely by showing a millennial face with millennial-style greetings, ways of dressing, and jokes and recruiting candidates transparently and without dowries directly through social media. Feminism leadership is seen in PSI's focus on the role and representation of women in the world of politics and providing special facilities for women in the PSI office.